Upaya Guru Meningkatkan Keterampilan Sosial (Social Skill) Anak Usia 5-6 Tahun Dengan Menggunakan Metode Bermain Peran di Kober Insan Madani - Nurrohmah, Anyi; Hurri, Ibnu; Elnawati, Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to determine the efforts of teachers in improving social skills of children aged 5-6 years through the role-playing method in Kober Insan Madani. Social skills are children's ability to interact positively with others, including the ability to cooperate, share, and resolve conflicts. This study uses a qualitative descriptive approach with a case study method. Data was collected through observation, interviews, and documentation. The results of the study show that the role-playing method is effective in improving children's social skills. Through careful planning, creative execution, and structured evaluation, children learn to understand social roles, empathy, and how to communicate well. The obstacles found include the lack of attention of children during activities and the limitations of play facilities and infrastructure. However, these obstacles can be overcome by teacher innovation in providing interesting learning media and involving parents in supporting activities. This research provides benefits for teachers, parents, and educational institutions in improving early childhood social skills. The application of the role-playing method has been proven to be able to create a fun and educational learning experience, so that it can be one of the effective strategies in learning in early childhood education.